The fragility of law: constitutional patriotism and the Jews of Belgium, 1940 - 1945 - Fraser, David (Routledge-Cavendish, 2009)
The taxonomies of an anti-Jewish legal order -- The secretaries-general : passive collaboration, Belgian law and the Jews, 1940-45 -- The fragility of law: anti-Jewish decrees and Belgian legal elites -- Aryanization, legalized theft and Belgian law -- Belgian municipalities and the introduction of anti-Jewish decrees -- Brussels : passive collaboration and the Jews of the capital -- Communicating, informing, and deciding : the city of Brussels and passive collaboration 1941-44 -- Liôge and its Jews: Hebrew and Polish stores, June 1940 -- Hirsch & co : a case study of Aryanization in Belgium -- Belgian lawyers, Belgian judges, Jewish cases -- Constitutional patriotism and the fragility of law